EXCLUSIVE BREASTFEEDING BETWEEN WITH THE NUMBER OF ARI EXPERIENCING TO 7-59 MONTHS INFANTS IN THE WORK AREA COMMUNITY HEALTH CENTERS BULILI 2015 - Kurnia, Suci Annisa; Sumarni, Sumarni; Rupawan, I Kadek (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
Background : Acute Respiratory Infections (ARI) is a respiratory disease upper or lower and cause a spectrum of illnesses. In Indonesia, ARI is one of the causes of patient visits to health facilities, such as the clinic and the hospital. One of the factor risk of the incidence of ARI is not getting exclusive breastfeeding.Method : Analytic observational research with cross sectional approach. With a population of children aged 7-59 months who come to the health center of Bulili during 2015. Number of samples is 96 infants, obtained by purposive sampling. Diagnosis is based on history and physical examination according to the guidelines of the clinic. Status of exclusive breastfeeding was obtained from Kartu Menuju Sehat (KMS). Analysis of data is using statistical test Chi Square.Result : The result showed that infants who are not getting exclusive breastfeeding have a  greater risk for causing ARI compared to infants who are given exclusive breastfeeding. This is supported by Chi-Square where the value of p = 0.000 meaning there is a significant relationship between exclusive breastfeeding with the incidence of ARI.Conclusion : There is a significant correlation between exclusive breastfeeding on the incidence of ARI in children aged 7-59 months in health center of bulili palu 2015.   Keyword :, Acute Respiratory Infections (ARI), Exclusive Breastfeeding Latar Belakang : Infeksi Saluran Pernapasan Akut (ISPA) adalah penyakit saluran pernapasan atas atau bawah dan menimbulkan berbagai spektrum penyakit. Di Indonesia ISPA merupakan salah satu penyebab kunjungan pasien ke sarana kesehatan, yaitu ke puskesmas dan ke RS. Salah satu faktor resiko kejadian ISPA adalah tidak mendapatkan ASI eksklusif.Metode : Penelitian observasional analitik dengan pendekatan Cross Sectional. Dengan populasi balita usia 7-59 bulan yang datang ke Puskesmas Bulili selama periode tahun 2015. Jumlah sampel 96 balita, diperoleh dengan cara  purposive sampling. Diagnosis berdasarkan anamnesis dan pemeriksaan fisik sesuai pedoman puskesmas. Status ASI eksklusif didapatkan dari Kartu Menuju Sehat (KMS). Analisis data menggunakan uji statistik Chi Square .Hasil : Dari hasil penelitian di dapatkan bahwa balita yang tidak diberikan ASI eksklusif lebih beresiko mengalami ISPA dibandingkan dengan balita yang diberikan ASI eksklusif. Ini didukung dengan uji Chi-Square dimana nilai p= 0,000 yaitu terdapat hubungan yang  bermakna antara pemberian ASI eksklusif dengan kejadian ISPA.Simpulan : Ada hubungan yang bermakna antara pemberian ASI eksklusif terhadap kejadian ISPA pada balita usia 7-59 bulan di wilayah kerja Puskesmas Bulili Kota Palu Tahun 2015.  Kata Kunci : Infeksi Saluran Pernapasan Akut (ISPA), ASI Eksklusif